Modelling Customers Lifetime Value For Non-Contractual Business - Riyanto Riyanto; Abdul Azis (International Journal of Informatics and Information Systems, 2021)
Due to the increasing importance placed on customer equity in today's business environment, many companies are focusing on the notion of customer loyalty and profitability to increase market share. Building a successful Customer Relationship Management (CRM), a company starts from identifying true value and customer loyalty because customer value can provide basic information to spread more targeted and personalized marketing. In this paper, customer lifetime value (CLV) is used for customer segmentation in non-contracted businesses. The results obtained from this study are very acceptable. CLV has successfully analyzed and produced a fairly strong assumption about the value possessed by each customer whether they will make a return transaction or not.